Pollination Efficacy of Stingless Bee (Tetragonula pagdeni) to Increase Yield of Bitter Guard in the Fields - เถียรวรกานต์ ผู้ช่วยศาสตราจารย์ ดร. ณัฏฐ์พัชร; ยะปะนัน ละไม; ตั้งศิริมงคล จิตติมา; โทผล ผู้ช่วยศาสตราจารย์ ดร.สุชาดา (Journal of Food Health and Bioenvironmental Science, 2017)
This study examined the pollination efficacy of the silver hair stingless bee (Tetragonula pagdeni) to increase the yield of bitter gourd in the experimental fields of Hortigenetic Research (S.E. Asia) Limited, Chiangmai during October 2015 - February 2016. The purposes of this study were to determine the pollination efficiency of T. pagdeni to increase the yield of bitter gourd, the optimal ratio of stingless bee hives per rai, and the economic value by comparing the yields with the control plot. The non-stingless bee plots contained 4, 8, or 12 stingless bee hives per rai. The study revealed that the silver hair stingless bee affected pollinating and increased the yield of bitter gourd in the field. The experimental plots with 4, 8, and 12 stingless bee hives per rai significantly increased yield per rai by approximately 60.12, 85.40, and 133.67 percent in addition to increased yield weights of 70.50, 101.77, and 161.46 percent, respectively, relative to the non-stingless bee plot. Moreover, in economic analysis aspects, the study showed that 4-12 stingless bee plots had higher net income than the non-stingless bee plot at 10,900-20,698 baht in the first year; furthermore, the net income increased by 60.8-105.6 percentage in the second year. The results of the benefit-cost ratio analysis for bitter gourd production in one rai showed that plots with 12 hives of stingless bee per rai produced the most profit.